Sams Teach Yourself Samsung GALAXY Tab in 10 Minutes - Kelly, James (Sams, 2011)
Sams Teach Yourself Samsung Galaxy Tab" in 10 Minutes offers straightforward, practical answers for fast results. By working through the 10-minute lessons, you'll learn everything you need to know to quickly and easily get up to speed on the Samsung GALAXY Tab. Step-by-step instructions walk you through the most common questions, issues, and tasks ... "Did You Know?" tips offer insider advice and shortcuts ... "Watch Out!" alerts help you avoid problems. Sams Teach Yourself Samsung Galaxy Tab" in 10 Minutes will provide beginner and experienced users with fast at a glance tips pointing out helpful shortcuts and solutions, cautions to help avoid common Samsung Galaxy Tab pitfalls, and is written in a clear easy to understand format. The Galaxy Tab offers the following features, all of which are covered in this book: " Integrated webcam " 3 megapixel camera " Built-in GPS " Expandable memory (up to 32GB) " Adobe Flash support " Android 2.2 operating system and the Android Market (for apps) " 3G support (carrier independent) and WiFi support Running the Android 2.2 Froyo operating system, the Galaxy Tab provides the consumer access to over 80,000 apps in the Android Market, along with access to digital books (via Amazon.com, for example), including the ePub format.